THE ANALYSIS OF SERVICES QUALITY EDUCATION BY TEACHER’S PROFESSION IN THE MINIMUM OF SERVICE STANDARDS - Nurismilida Nurismilida (FIP Unimed, 2016)
ABSTRACTThis article will discuss the importance of quality education services and their implementation in education with the teacher as the executing subject. Service quality of education itself has a specific standard as the reference for the implementation of educational services that must be obey, this standard issued by the Ministry of Education in National Education Minister Regulation No. 15 in 2010 entitle with The Minimum Of Service Standards. This research was conducted by sending an email containing a questionnaire to some teachers at SMK 2 Langsa and MTS Galih Agung Lau Bakery in March 2016. The population is all teachers in the school and a sample of eight people. Based on the research results, the authors conclude that the condition of teachers in these schools understand enough about quality education services but do not know on Minimum Service Standards. Keywords: Minimum Service Standards, Quality of educational services